Getting Under the Skin: How Social Adversity and Psychosocial Adversity Affect the Immune System in Health and Ageing - Reddy, Conor Joseph (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2026)
The stark disparities in health outcomes revealed during the COVID-19 pandemic have highlighted an urgent need to understand the biological consequences of social inequality. This thesis explores the overall hypothesis that many of the health outcomes caused by social inequality are due to alterations within the immune system; specifically, it investigates how socioeconomic status (SES), homelessness, and psychosocial adversity shape trajectories of immune ageing and impact on vaccine responsiveness using two linked human cohorts: Assessing Effects of SES-Associated Psychosocial Stress on Vaccine-Induced Immunity to SARS-CoV-2 (AESS-Vax, n=164) and Premature Ageing in long-Term Homeless Adults (PATH, n=59). Participants were stratified by SES and housing status, and provided detailed sociodemographic, clinical, and psychosocial data alongside biological samples. Immune parameters assessed included SARS-CoV-2 vaccine-induced humoral and cellular immunity, multiplex cytokine profiling, and spectral cytometry-based immunophenotyping of lymphocyte subsets. In AESS-Vax, total anti-Spike antibody levels were lower in infection-naive low SES participants at both 1216 and 2228 weeks post-vaccination. Similarly, antigen-specific IFN- production following stimulation of whole blood with Spike peptides and protein was diminished in low SES participants at both 1216 and 2228 weeks following a third, booster dose of BNT162b2. Structural equation modelling did not detect significant mediation by psychosocial stress; however, post-hoc power analyses indicated the study was underpowered to detect such effects, a limitation compounded by inconsistent collection of stress measures across participants. This is the first study to comprehensively profile post-vaccine immune responses and broad cellular immunophenotypes in socially excluded and homeless individuals. To explore the broader range of social effects on immunity, a combined cohort comprised of both PATH and AESS-Vax participants was used (n=173).In an immune proteome screen of serum samples from this cohort, eight cytokines were found to be elevated in homeless compared to housed individuals, including TNF-, IL-1, IL-6, IL-10, IL-12p70, IL-18, IL-4, and IL-2. Differences were also observed by SES, though of lesser magnitude. Notably, the differences associated with homelessness persisted after adjusting for age, sex, smoking history, and alcohol consumption. These cytokine profiles are consistent with observations of the immune profile seen in "inflammageing", highlighting homelessness as a particularly strong immunological stressor. Furthermore, high-dimensional immunophenotyping revealed that participants from low SES backgrounds had reduced frequencies of naive CD4+ and CD8+ T cells. They also had expanded populations of CD57+, KLRG1+, and TEMRA cells, features associated with terminal differentiation, immune exhaustion, and cellular senescence. These differences were independent of age, sex, and CMV serostatus, and were most pronounced in those with histories of chronic psychosocial stress and social exclusion. Together, these findings define an adversity-associated immunophenotype marked by persistent inflammation, altered lymphocyte composition, and diminished functional immune responses to vaccination. This social adversity associated immunophenotype may represent a mechanism by which social disadvantage becomes biologically embedded, accelerating immune ageing and compromising host defence. These results underscore the importance of integrating social context into models of human immunity and ageing.
APPROVED
Keywords: psychoneuroimmunology; inclusion health; immune ageing; homelessness; psychosocial stress and the immune system; translational immunology; ageing in homelessness; social determinants of health